1994
DOI: 10.1083/jcb.125.2.381
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of the yeast actin cytoskeleton and its association with the plasma membrane.

Abstract: Abstract. We characterized the yeast actin cytoskeleton at the ultrastructural level using immunoelectron microscopy. Anti-actin antibodies primarily labeled dense, patchiike cortical structures and cytoplasmic cables. This localization recapitulates results obtained with immunofluorescence light microscopy, but at much higher resolution. Immuno-EM double-labeling experiments were conducted with antibodies to actin together with antibodies to the actin binding proteins Abplp and cofilin. As expected from immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
273
0
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(296 citation statements)
references
References 32 publications
22
273
0
1
Order By: Relevance
“…We did not detect any actin cable-like structures in our preparations, nor are cables apparent in intact spheroplasts, which lack obvious cell polarity. Our results extend upon a previous model in which actin filaments wind around finger-like invaginations of the plasma membrane (Mulholland et al, 1994). We show that actin patches are conical or mound-like structures rising out of the plasma membrane and suggest that they are composed of short filaments arranged into an apparently cross-linked scaffold that surrounds a membrane core.…”
Section: Ultrastructure Of Cortical Actin Patches In Yeastsupporting
confidence: 76%
See 2 more Smart Citations
“…We did not detect any actin cable-like structures in our preparations, nor are cables apparent in intact spheroplasts, which lack obvious cell polarity. Our results extend upon a previous model in which actin filaments wind around finger-like invaginations of the plasma membrane (Mulholland et al, 1994). We show that actin patches are conical or mound-like structures rising out of the plasma membrane and suggest that they are composed of short filaments arranged into an apparently cross-linked scaffold that surrounds a membrane core.…”
Section: Ultrastructure Of Cortical Actin Patches In Yeastsupporting
confidence: 76%
“…However, actin filaments do not show up well in the crowded yeast cytoplasm, except for rare actin cables in Saccharomyces cerevisiae and pathogenic yeasts (Adams and Pringle, 1984;Kopecka et al, 2001;Yamaguchi et al, 2002), cytoplasmic "filasomes" distinct from cortical patches in fission yeast (Kanbe et al, 1989;Takagi et al, 2003), and aberrant filamentous actin structures in mutant budding yeast defective in endocytosis (Sekiya-Kawasaki et al, 2003). Immunolabeled thin sections have in some cases revealed finger-like invaginations of the plasma membrane apparently entwined in an actin helix (Mulholland et al, 1994). However, these structures are two-dimensional and thus provide limited information about geometry and spatial relations within cortical actin patches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At cytokinesis, the actin cytoskeleton is reorganized and actin patches are relocalized to the mother-daughter neck where the cell wall is modified for cell separation. The mechanisms by which actin mediates polarized secretion are not well understood, but it has been shown that cortical actin patches are associated with the cell surface through an invagination of the plasma membrane (Mulholland et al, 1994) and it has been suggested that components of the secretory pathway (endoplasmic reticulum [ER] and Golgi) could be transported into the bud to direct localized growth presumably via an actin-dependent mechanism (Preuss et al, 1992).A variety of proteins have been shown to be required for either bud emergence or for bud site selection (for recent reviews see Bretscher et al, 1994;Chant, 1994; Welch and Drubin, 1994). CDC42, encoding a small GTP-binding protein, and several genes encoding its regulators are involved in bud emergence: cells mutated in these genes arrest as large unbudded cells with a disorganized actin cytoskeleton and delocalized chitin.…”
mentioning
confidence: 99%
“…Immunoelectron microscopy indicated that at least some of the actin patches represent coils of actin filaments surrounding membrane invaginations (Mulholland et al, 1994). These structures might anchor the cytoskeleton to the plasma membrane.…”
Section: Saccharomyces Cerevisiaementioning
confidence: 99%